1986
DOI: 10.1128/jb.167.2.487-491.1986
|View full text |Cite
|
Sign up to set email alerts
|

Genetic rearrangements of a Rhizobium phaseoli symbiotic plasmid

Abstract: Different structural changes of the Sym plasmid were found in a Rhizobium phaseoli strain that loses its symbiotic phenotype at a high frequency. These rearrangements affected both nif genes and TnS mob insertions in the plasmid, and in some cases they modified the expression of the bacterium's nodulation ability. One of the rearrangements was more frequent in heat-treated cells, but was also found under standard culture conditions; other structural changes appeared to be related to the conjugal transfer of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…We have found that pSym of CFN299 belongs to a different compatibility group than does pSym of CFN42 (the standard reference strain with nifH reiterations), since we have been able to maintain both symbiotic plasmids in GMI9023 (unpublished results). Other R. phaseoli plasmids show differences; pSym9 is a nonconjugative plasmid of 275 megadaltons (16), pRP2J1 is a conjugative plasmid of 190 megadaltons (20), and in pSym of CFN23 symbiotic instability is associated with genetic rearrangements (29). It would be interesting to see whether nodulation genes with P. vulgaris specificity are equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that pSym of CFN299 belongs to a different compatibility group than does pSym of CFN42 (the standard reference strain with nifH reiterations), since we have been able to maintain both symbiotic plasmids in GMI9023 (unpublished results). Other R. phaseoli plasmids show differences; pSym9 is a nonconjugative plasmid of 275 megadaltons (16), pRP2J1 is a conjugative plasmid of 190 megadaltons (20), and in pSym of CFN23 symbiotic instability is associated with genetic rearrangements (29). It would be interesting to see whether nodulation genes with P. vulgaris specificity are equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that frequent genomic rearrangements are probably confined to certain regions of the genome. Soberon-Chavez et al (23) reported rearrangements that alter the symbiotic plasmid of another R. phaseoli strain with loss of nif genes as well as nodulation ability. In the case of some Archaebacteria, which have many repeated DNA sequences and present frequent genomic rearrangements (21), these appear to be circumscribed to only some zones of the genome, having a high A+T content (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…Our present observations do rule out the occurrence of large-scale DNA rearrangements in mature bacteroids of B. japonicum. Genomic rearrangements are common in some Rhizobiaceae, notably in R. leguminosarum biovar phaseoli (13,39,40). Furthermore, repeated DNA sequences exist in B. japonicum (20), Sinorhizobium fredii (26,31), and other Rhizobiaceae (12 [7,15]), yet it still leaves questions unresolved.…”
mentioning
confidence: 99%